2022
DOI: 10.3390/ijerph191610065
|View full text |Cite
|
Sign up to set email alerts
|

Travel Behaviour of Vulnerable Social Groups: Pre, during, and Post COVID-19 Pandemic

Abstract: Since the emergence of COVID-19, travel restrictions due to the pandemic have influenced several activities, in particular the mobility patterns of individuals. Our main goal is to draw the attention of scholars and policy makers to a specific segment of the population, namely (1) older people, (2) persons with disabilities (PwDs), (3) females, and (4) low-income population that are more vulnerable for travel behaviour change due to crisis such as the COVID-19 pandemic. This article systematically reviews the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 50 publications
2
5
1
Order By: Relevance
“…above 65 years of age) compared to younger people [ 9 ]. The latter finding is in contrast to other research reporting that particularly older people and vulnerable people were affected by COVID-19-related mobility restrictions [ 12 , 31 , 40 ]. The specific circumstances during the COVID-19 pandemic should be considered when interpreting the results of the study at hand.…”
Section: Discussioncontrasting
confidence: 99%
“…above 65 years of age) compared to younger people [ 9 ]. The latter finding is in contrast to other research reporting that particularly older people and vulnerable people were affected by COVID-19-related mobility restrictions [ 12 , 31 , 40 ]. The specific circumstances during the COVID-19 pandemic should be considered when interpreting the results of the study at hand.…”
Section: Discussioncontrasting
confidence: 99%
“…The following study confirmed the impact of the pandemic on public transport and also dealt with the issue of the gender gap in travel behaviour during the development of the pandemic. This contribution, as well as the results of our research, highlighted the increased risk of infection in women [76]. A study in Belgium about mobility indicated a high proportion of infected women out of the total number of people infected with the COVID-19 virus.…”
Section: Discussionsupporting
confidence: 73%
“…Besides, the age of the respondents is related to the choice of transport mode after the lockdown. The positive relationship with public transport users shows that older people are (1.5 times) more likely to use public transport after lockdown meaning that older adults preferred using public transport after the pandemic and younger adults preferred using active mode versus public transport that could be due to the better accessibility of public transport for older people in the city ( Dadashzadeh et al, 2022 ; Guida & Carpentieri, 2021 ). It is noteworthy that the survey was carried out when people were still under the stay-at-home measure (lockdown) and the modal choice after lockdown represents their preferences and interests for their daily travel after lockdown.…”
Section: Discussionmentioning
confidence: 99%